ANALISIS KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN UNTUK MENCAPAI PENERIMAAN PAJAK DI KECAMATAN SETIABUDI DKI JAKARTA - Aditya Tirta Wiguna (Sekolah Pascasarjana Perbanas Jakarta, 2021)
The study analysis of the tax payer compliance in paying land and building tax to achieve tax receiving in setiabudi district DKI Jakarta. The population in this study is sub district Setia Budi DKI Jakarta. This study analyses the factors that increase tax payer compliance, the efforts that has been made by the sub district office in improving compliance and the obstacles faced by the sub district office in increasing tax payer compliance in paying land and building taxes. Result of analysis found factors that increase tax payer compliance 1. Lack of information and counselling from the government to tax payer. 2.Lack of control and supervision from the government to the office, 3. Individual atmosphere. For the effort made by the Setiabudi district office to improver tax payer compliance in paying land and building tax 1. Giving counselling to tax payer, 2.Improving service to tax payer, 3. Giving reward. And for obstacle faced by the Setiabudi district office in improving tax payer compliance to pay land and building tax 1. Lack of interest of tax payer in following counselling, 2. Technical problem, 3. Increasing in land and building tax expense. Keyword :Tax payer, compliance, land and building tax